1989
DOI: 10.1109/10.32106
|View full text |Cite
|
Sign up to set email alerts
|

FES and spasticity

Abstract: A model of hemiplegic spasticity based on electromyographical and biomechanical parameters measured during passive muscle stretching is presented. Two components of spasticity can be distinguished--phasic and tonic. This classification depends on the pattern of stretch reflex activity which can be either phasic or tonic as well as on the muscle stretch/tension characteristic. Stretch reflex, as a control loop, is in phasic spasticity characterized by increased sensitivity to velocity of stretching. In tonic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…used extensively over several decades as an effective means to reduce or reverse muscle atrophy and to obtain some functional recovery by rehabilitation strategies for spinal cord injury patients, [1][2][3][4][5] including those paraplegics with permanent and complete denervation of the legs (complete Conus and Cauda Equina Syndrome). [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The benefits of this technology are being expanded into other areas, and FES has been recently utilized for injury rehabilitation and performance enhancement in horses.…”
Section: Functional Electrical Stimulation (Fes) Has Beenmentioning
confidence: 99%
“…used extensively over several decades as an effective means to reduce or reverse muscle atrophy and to obtain some functional recovery by rehabilitation strategies for spinal cord injury patients, [1][2][3][4][5] including those paraplegics with permanent and complete denervation of the legs (complete Conus and Cauda Equina Syndrome). [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The benefits of this technology are being expanded into other areas, and FES has been recently utilized for injury rehabilitation and performance enhancement in horses.…”
Section: Functional Electrical Stimulation (Fes) Has Beenmentioning
confidence: 99%
“…Spasticity of spinal origin can be similar but tends to involve more flexor spasms of the lower limbs. Stefanovska et al divided spasticity into "tonic" and "phasic" components [20][21], depending on whether sensitivity to velocity or length of stretch increased. Study of spasticity in general is also complicated by the fact that both involvement of different descending tracts [22] and the amount of time after an upper motor neuron lesion [11] can influence the nature of the deficit and the response to therapy.…”
Section: Spasticitymentioning
confidence: 99%
“…PNS in paraplegia from SCI has also been shown to aid gait by generating a knee/hip withdrawal reflex [37], although the effects on these joints in MS seem less clear [39]. Although there has been some investigation into percutaneous and implanted systems [20][21]40], surface FES systems are widely available and have fewer contraindications. PNS has been investigated both for its potential gait improvement while the patient is actively using the device, the "orthotic effect," [41] and for its rehabilitation benefit after the device is no longer in use, the "therapeutic effect."…”
Section: Functional Electrical Stimulationmentioning
confidence: 99%
“…It has been reported that warming up prior to, for example, standing up or ambulation prevents the occurrence of spasticity (STEFANOVSKA et aL, 1989). (ii) Stimulation onset and burst duration were optimized (Section 3.3).…”
Section: Protocolmentioning
confidence: 99%